The impact of feedback literacy on reflective learning types in Chinese high school students: based on latent profile analysis - Gong, Yuhong; Zhang, Shang; Zhang, Ting; Yi, Xinfa (Frontiers in Psychology, 2025)
ObjectiveExisting research has not yet thoroughly explored the mechanism through which feedback influences reflective learning, failing to effectively guide teaching practice. This study shifts the research focus from a singular feedback to a comprehensive exploration of feedback literacy, and delves into the internal dynamics of groups to investigate the sub-group characteristics of reflective learning. It aims to provide more detailed empirical evidence, as well as more targeted and operational improvement recommendations for reflective learning practice.Methodsthis study has developed a research design that encompasses latent variable profile analysis and subsequent analyses. A total of 704 Chinese high school students (45.31% male, 54.69% female) effectively participated in the surveys using the Feedback Literacy Scale and the Reflective Thinking Level Questionnaire, along with standardized academic examinations organized by their schools.Resultsthe LPA results indicated the presence of four latent types of reflective learning among Chinese high school students, named as follows: the Low Reflective Learning Group (LRLG, 22.9%), the Low Habits-high Understanding Learning Group (LHHULG, 15.6%), the Moderate Reflective Learning Group (MRLG, 46.3%), and the High Reflective Learning Group (HRLG, 15.2%). It revealed that feedback literacy, age, grade, and gender are closely correlated with the latent types of reflective learning. Meanwhile, a close correlation between the latent types of reflective learning and achievements in Mathematics and English.Conclusionsstudents in different latent types of reflective learning groups exhibit distinct characteristics in habitual behavior, understanding, reflection, and critical reflection. As age and grade level increase, the number of students in the HRLG decreases; Males tend to HRLG, MRLG and LHHULG, while females tend toward LRLG. The elicitation, enactment, commitment, and readiness within feedback literacy can significantly influence the latent type grouping of reflective learning, and compared to the LRLG, the MRLG, LHHULG, and HRLG exhibit better performance in English and mathematics. The conclusions of this study not only help educators understand the characteristics of subgroups within latent types of reflective learning but also guide teachers in utilizing the identified relationship between feedback literacy and latent types of reflective learning to implement differentiated instruction or personalized guidance.